2019
DOI: 10.1159/000500589
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Recognition in Kindergarten Children

Abstract: Background/Aims: Recognition and understanding of emotions are essential skills in nonverbal communication and in everyday social functioning. These are already evident in infancy. We aimed to compare how young children recognize facial emotional expressions from static faces versus vocal emotional expressions from speech prosody. Methods: Participants were 313 kindergarten children (162 girls, mean age = 51.01, SD 9.65 months; range 36–72). The design consisted of a visual and an auditory block (with 45 rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
3
1
Order By: Relevance
“…Joy was more recognised and mistakenly chosen for anger or sadness, probably due to a positivity bias in children [6]. Overall, participants of our study, who had been exposed to facemasks for nearly a year, recognized emotions on pictures better than reported in previous research, even with facemasks [1,6]. This study has several limitations including the generalizability of its findings using static pictures instead of live actors, and the validity of the outcomes.…”
Section: We Built the Experiments With E-prime® [4] The Ethics Commit...contrasting
confidence: 66%
See 1 more Smart Citation
“…Joy was more recognised and mistakenly chosen for anger or sadness, probably due to a positivity bias in children [6]. Overall, participants of our study, who had been exposed to facemasks for nearly a year, recognized emotions on pictures better than reported in previous research, even with facemasks [1,6]. This study has several limitations including the generalizability of its findings using static pictures instead of live actors, and the validity of the outcomes.…”
Section: We Built the Experiments With E-prime® [4] The Ethics Commit...contrasting
confidence: 66%
“…This has prompted worries about the ability of young children to recognize emotions and the possible impact on their development. Without face masks, preschoolers aged 36 to 72 months had a rate of correctly identified emotions on pictures of 11.8% to 13.1% . Recent studies using photographs with digitally added face masks showed that participants had worse emotional recognition of the images with face masks; the first of these tested preschoolers on a smartphone at home, and the second tested children aged 7 to 13 years.…”
mentioning
confidence: 99%
“…Emotion recognition has been widely studied and applied in various fields. For example, emotion recognition is used in medical care [4][5][6], education [7][8][9], service industry [10][11][12], and other fields. For emotion recognition methods, there are mainly scale methods [13,14], machine learning [15][16][17], and deep learning algorithms [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to acquire emotion recognition is a continual process that depends on the developmental phases of human beings and improves significantly with age [Covic et al, 2020]. The children were reported to be able to recognize facial emotions of happiness and surprise at 3 months [Young-Brownee and Rosenfeld, 1977], anger at 4 months [Barrera and Maurer, 1981], and fear at 7 months [Kotsoni et al, 2001] of age.…”
Section: Introductionmentioning
confidence: 99%